Effects of a digital visual art learning intervention in healthy older adults: a pilot randomized controlled trial - Uno, Akari; Browne, Ryan; Shinada, Takamitsu; Takahashi, Michio; Soga, Keishi; Du, Yegang; Abiko, Fumihira; Taki, Yasuyuki (Frontiers in Aging, 2025)
IntroductionThis study aimed to examine the effects of a digital visual art learning intervention on the cognitive and psychological functions of healthy older adults with no prior experience in art.MethodsAn open-label pilot randomized controlled trial was conducted, with participants (mean age = 69.43 ± 2.70 years) aged 65 to 74 assigned to either an intervention (n = 37) or control (n = 35) group. Cognitive and psychological functions were assessed before and after 20 sessions of digital visual art learning. In each session, participants mainly worked on lectures and prepared tasks related to basic themes in art. In the final stage, each participant engaged in individual creative activities and aimed to complete their works.ResultsIn the Frontal Assessment Battery, which evaluates frontal lobe function, a significant trend was observed in the interaction between group and time (p = 0.062), and although an improvement trend was observed in the intervention group, the change did not reach statistical significance.ConclusionThese findings suggest that digital art could potentially enhance executive function in older adults, providing important insights into its applicability within this population.Clinical trial registrationhttps://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000058589, identifer UMIN000051427